Análisis multivariado a los factores relacionados con el aprendizaje móvil en la educación superior en Colombia - Estrada-Villa, Erika Juliana (2018)
This article shows the elements related to mobile learning in higher education; a multivariate analysis (the main focus of this article) on these elements was performed. For this, mixed research was conducted that took part of the results obtained on a previous research project. In these results, fourteen elements were identified; now, this article reduces them to three through a multifactorial analysis. Besides, to collect the data, a Likert-type instrument was applied to 30 university researchers. To process the data a multivariate analysis was implemented, resulting in the following elements: the training element and the student’s characteristics; the lack of management that correlates with the lack of m-learning guidelines and lack of infrastructure. In conclusion, the elements extracted should be taken into account when drawing guidelines to include mobile learning in higher education, as well as teacher training plans, in response to what students require.